2009
DOI: 10.1021/jm900697r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of a New Generation of Orally Efficacious Benzimidazole-Based Poly(ADP-ribose) Polymerase-1 (PARP-1) Inhibitors as Anticancer Agents

Abstract: Small molecule inhibitors of PARP-1 have been pursued by various organizations as potential therapeutic agents either capable of sensitizing cytotoxic treatments or acting as stand-alone agents to combat cancer. As one of the strategies to expand our portfolio of PARP-1 inhibitors, we pursued unsaturated heterocycles to replace the saturated cyclic amine derivatives appended to the benzimidazole core. Not only did a variety of these new generation compounds maintain high enzymatic potency, many of them also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
45
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…In addition, it was orally bioavailable and possessed good in vivo efficacy in a murine melanoma model (Penning et al, 2010). Other benzimidazole-4-carboxamide analogues as PARP-1 inhibitors with high cellular activity were also presented (Tong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was orally bioavailable and possessed good in vivo efficacy in a murine melanoma model (Penning et al, 2010). Other benzimidazole-4-carboxamide analogues as PARP-1 inhibitors with high cellular activity were also presented (Tong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tong et al described the synthesis of compound 55 showed the best activity with EC 50 value of 3.7 µM [22]. Oxadiazole compounds 56 and 57 were appeared as potent members of anticancer family of drugs [23].…”
Section: Introductionmentioning
confidence: 99%
“…As a bioisostere of indole, benzimidazole skeleton was incorporated into the target compounds. This is due to the fact that benzimidazoles have been frequently found to display a variety of biological activities such as anticancer [25] and antiproliferative properties [26]. Moreover, compared with the indole ring, the benzimidazole moiety more readily binds with a variety of enzymes and receptors in biological systems through diverse weak interactions, thereby exhibiting broad bioactivities.…”
Section: Introductionmentioning
confidence: 99%